Women empowerment and sustainable development - Kumar, Bipin, Dr. (New Delhi : Regal, 2009)
Contributed articles on Indian context.
Includes index.
Includes bibliographical references.
Keywords: Women -- Employment -- India; Sustainable development -- India; Self-help groups -- India; Women in development -- Government policy -- India; Rural women -- Government policy -- India; Businesswomen -- India